Do Funds Make More When They Trade More? - PÁSTOR, ĽUBOŠ; STAMBAUGH, ROBERT F.; TAYLOR, LUCIAN A. (Journal of Finance, 2017)
ABSTRACT We model fund turnover in the presence of time‐varying profit opportunities. Our model predicts a positive relation between an active fund's turnover and its subsequent benchmark‐adjusted return. We find such a relation for equity mutual funds. This time‐series relation between turnover and performance is stronger than the cross‐sectional relation, as the model predicts. Also as predicted, the turnover‐performance relation is stronger for funds trading less‐liquid stocks and funds likely to possess greater skill. Turnover is correlated across funds. The common component of turnover is positively correlated with proxies for stock mispricing. Turnover of similar funds helps predict a fund's performance.